The Arab Spring and the sustainability of women’s rights - Roumate, Fatima (2013)
Two years later, the consequences of the Arab Spring are a masculinity of powers and a retreatregarding the rights of women who paid a high price for the change. Subsequently, the Islamistscome to power after the Arab revolutions that talk about democratization, but without the rights ofwomen. The democratization that promotes the parental rights and affects profoundly the dignityof the other half of society. This brings to the table the issue of safety or even legal certainty.The sustainability of women’s rights is a risk to safety and a threat to the achievements of women’sgroups after years of militancy language. It has a cost and a negative impact on the developmentof the Arab world.Indeed, sustainability also implies the legitimacy of governors chosen by men and women who arenot able to protect the rights of half of society who has chosen and accepted them. This consideringthat the social contract is only the selection and acceptance of leaders who must, in return, ensurethe safety and protect the human rights of governed men and women.